The Gateway to Computer Science Excellence
+10 votes
739 views
Let $A = \begin{bmatrix} a_{11} && a_{12} \\ a_{21} && a_{22} \end{bmatrix} \text { and } B = \begin{bmatrix} b_{11} && b_{12} \\ b_{21} && b_{22} \end{bmatrix}$ be two matrices such that $AB=I$. Let $C = A \begin{bmatrix} 1 && 0 \\ 1 && 1 \end{bmatrix}$ and $CD =I$. Express the elements of $D$ in terms of the elements of $B$.
in Linear Algebra by Veteran (52.2k points) | 739 views

4 Answers

+29 votes
Best answer

$AB = I$, B is equal to the inverse of $A$ and vice versa.

So, $B= A^{-1}$

Now $CD =I$, $C$ is equal to the inverse of $D$ and vice versa.

So, $D =C^{-1}$ ​​​​​​

​$=\left(A.\begin{bmatrix} 1& 0 \\ 1&1 \end{bmatrix}\right)^{-1}$

Remark: $(AB)^{-1} = B^{-1}A^{-1} $

​$=\begin{bmatrix} 1& 0 \\ 1&1 \end{bmatrix}^{-1}.A^{-1}$

​$=\begin{bmatrix} 1& 0 \\ {-1}&1 \end{bmatrix}.B$

 ​$=\begin{bmatrix} b_{11}& b_{12} \\ b_{21}-b_{11}&b_{22}-b_{12} \end{bmatrix}$

by Loyal (6.3k points)
edited by
0
which formula in last line?
+1
^ Multiplication of matrices $ I  and  B $  :)
+1 vote

AB=CD

let x=[ 1  0 ]    

         [ 1  1]

AB=AXD

D=inv(X) *B

ANS IS          [b11                b12  ]

                     [ b21-b11   b22-b12  ]

by Loyal (8.2k points)
+1 vote
Suppose D = $\begin{bmatrix} d_{11} & d_{12} \\ d_{21} & d_{22} \end{bmatrix}$

Now, CD = AB  where C= A$\begin{bmatrix} 1 & 0 \\ 1 & 1 \end{bmatrix}$

so,  A$\begin{bmatrix} 1 & 0 \\ 1 & 1 \end{bmatrix}$ = AB  [here A will be cancel out because on bothside A is a matrix]

$\begin{bmatrix} 1 & 0 \\ 1 & 1 \end{bmatrix}$ . $\begin{bmatrix} d_{11} & d_{12} \\ d_{21} & d_{22} \end{bmatrix}$ = A$\begin{bmatrix} b_{11} & b_{12} \\ b_{21} & b_{22} \end{bmatrix}$

$\begin{bmatrix} d_{11} & d_{12} \\ d_{11} + d_{21} & d_{12} + d_{22} \end{bmatrix}$ = $\begin{bmatrix} b_{11} & b_{12} \\ b_{21} & b_{22} \end{bmatrix}$

two matrix equally same means they are element wise equal.by this we can easily calculate, D = $\begin{bmatrix} b_{11} & b_{12} \\ b_{21} - b_{11} & b_{22} - b_{12} \end{bmatrix}$
by Active (3.1k points)
0
in 3rd line why have you not written D after substituting value of C ?
0 votes
Let |1 0| is X.

      |1 1|

C = AX

AB = I, A = 1/B

C = (1/B)*X

CD = (1/B)*XD = 1*I XD = B. // left multiplication by B

D = (1/X)*B. // left multiplication by 1/X

(1/X)*B = |1 -1| * |b11 b12|

                |0 1|     |b21 b22|

            = |(b11-b21) b12-b22|

               | b21 b22 |

            = D
by Veteran (60.6k points)
edited by
+1
answer is wrong

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
50,645 questions
56,597 answers
195,838 comments
102,146 users